Short-term effect of polyethylene glycol loxenatide on weight loss in overweight or obese patients with type 2 diabetes: An open-label, parallel-arm, randomized, metformin-controlled trial - Cai, Hongyu; Chen, Qianqian; Duan, Yale; Zhao, Yue; Zhang, Xiujuan (Frontiers in Endocrinology, 2023)
Objective: Polyethylene glycol loxenatide (PEG-Loxe) is a novel, once-weekly glucagon-like peptide 1 receptor agonist that is approved in doses of 0.1 mg and 0.2 mg for the treatment of type 2 diabetes mellitus (T2DM). However, no clinical trials have been designed to determine the effect of 0.3 mg PEG-Loxe on weight loss in overweight or obese patients with T2DM. This trial aimed to evaluate the short-term effect of 0.3 mg PEG-Loxe, injected subcutaneously once weekly, for weight management in overweight or obese patients with T2DM. Methods: This 16-week, open-label, parallel-arm, randomized, metformin-controlled trial was conducted at Shandong Provincial Hospital in Shandong, China. Patients with T2DM, who were overweight or obese (body mass index ≥ 25.0 kg/m2) and had been treated with lifestyle interventions or a combination with oral antidiabetic drug monotherapy were randomized (2:1) to receive 0.3 mg PEG-Loxe or 1500 mg metformin. The primary endpoint was a change in body weight from baseline to week 16. Results: Overall, 156 patients were randomized and exposed to treatment. Weight loss was 7.52 kg (8.37%) with PEG-Loxe and 2.96 kg (3.00%) with metformin, with a between-group difference of 4.55 kg (95% CI, 3.43 to 5.67) (P < 0.001). A significantly higher proportion of patients lost ≥5% (61.5% vs. 25.0%) or 10% (26.9% vs. 5.8%) body weight in the PEG-Loxe group than in the metformin group (P < 0.01). Additionally, PEG-Loxe resulted in marked improvements in several cardiovascular risk factors compared to metformin, including body mass index, waist circumference, visceral fat area, blood pressure, and lipid profile. PEG-Loxe and metformin displayed almost equal potency for glycemic control. The incidence of adverse events was 46.2% (48/104) and 44.2% (23/52) in the PEG-Loxe and metformin groups, respectively. Conclusion: In overweight or obese patients with T2DM, a once-weekly subcutaneous administration of PEG-Loxe for 16 weeks, in addition to lifestyle interventions or oral antidiabetic drug therapy, resulted in significantly greater weight loss compared to metformin. Additional trials are necessary to establish whether these effects can be maintained in the long term. Clinical Trial Registration: www.chictr.org.cn; Unique Identifier: ChiCTR2200057800.